Cellular softening mediates leukocyte demargination and trafficking, thereby increasing clinical blood counts - Fay, Meredith E; Myers, David R; Kumar, Amit; Turbyfield, Cory T; Byler, Rebecca; Crawford, Kaci; Mannino, Robert G; Laohapant, Alvin; Tyburski, Erika A; Sakurai, Yumiko; Rosenbluth, Michael J; Switz, Neil A; et al. (Proceedings of the National Academy of Sciences - PNAS, 2016)
Leukocytes normally marginate toward the vascular wall in large vessels and within the microvasculature. Reversal of this process, leukocyte demargination, leads to substantial increases in the clinical white blood cell and granulocyte count and is a well-documented effect of glucocorticoid and catecholamine hormones, although the underlying mechanisms remain unclear. Here we show that alterations in granulocyte mechanical properties are the driving force behind glucocorticoid- and catecholamine-induced demargination. First, we found that the proportions of granulocytes from healthy human subjects that traversed and demarginated from microfluidic models of capillary beds and veins, respectively, increased after the subjects ingested glucocorticoids. Also, we show that glucocorticoid and catecholamine exposure reorganizes cellular cortical actin, significantly reducing granulocyte stiffness, as measured with atomic force microscopy. Furthermore, using simple kinetic theory computational modeling, we found that this reduction in stiffness alone is sufficient to cause granulocyte demargination. Taken together, our findings reveal a biomechanical answer to an old hematologic question regarding how glucocorticoids and catecholamines cause leukocyte demargination. In addition, in a broader sense, we have discovered a temporally and energetically efficient mechanism in which the innate immune system can simply alter leukocyte stiffness to fine tune margination/demargination and therefore leukocyte trafficking in general. These observations have broad clinically relevant implications for the inflammatory process overall as well as hematopoietic stem cell mobilization and homing.